Relevance of AIDA Theory in Consumer Behavior in the Digital Era: A Systematic Literature Review 2018–2024 - Wijayanti, Irine Diana Sari; Murdapa, Purnama Andri (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The rapid development of digital technology and algorithm-driven platforms has significantly transformed consumer behavior and challenged the applicability of classical marketing communication models, including the Attention–Interest–Desire–Action (AIDA) framework. This study aims to systematically examine the relevance and adaptability of AIDA theory in the digital era and to develop a conceptual extension that reflects contemporary digital marketing practices. Using a Systematic Literature Review (SLR) approach based on the PRISMA 2020 protocol, this study analyzes 30 peer-reviewed articles published between 2018 and 2024 that address the application of AIDA in digital marketing and consumer behavior contexts. The findings indicate that the AIDA model remains conceptually relevant as a foundational framework for understanding consumer decision-making. However, each stage has undergone substantial transformation due to algorithmic personalization, user-generated content (UGC), influencer marketing, and instant transaction technologies. Digital algorithms play a critical role in shaping attention and interest, while desire is increasingly influenced by social proof and emotional engagement. Furthermore, technological features such as one-click purchasing and integrated digital payments significantly accelerate the transition from desire to action. Several studies also emphasize the importance of post-purchase engagement and satisfaction, highlighting the need to extend the traditional AIDA structure. Based on the synthesis, this study proposes an Algorithmic AIDCAS model (Attention–Interest–Desire–Conviction–Action–Satisfaction) as a managerial-oriented framework that captures the non-linear, feedback-driven nature of digital consumer behavior. This model offers both theoretical and practical contributions by bridging classical marketing theory with data-driven digital marketing management. The findings provide valuable insights for academics and practitioners in designing, implementing, and evaluating digital marketing strategies in dynamic business environments. Keywords: AIDA Theory; Consumer Behavior; Digital Marketing; Algorithmic Marketing; Systematic Literature Review.